Bacteriophate-Induced Functions in Escherichia coli K(λ) Infected with rII Mutants of Bacteriophage T4 - Rutberg, Blanka (1966)
Rutberg, Blanka (Karolinska Institutet, Stockholm, Sweden), and Lars Rutberg. Bacteriophage-induced functions in Escherichia coli K(λ) infected with rII mutants of bacteriophage T4. J. Bacteriol. 91:76–80. 1966.—When Escherichia coli K(λ) was infected with rII mutants of phage T4, deoxycytidine triphosphatase, one of the phage-induced early enzymes, was produced at initially the same rate as in r(+)-infected cells. Deoxyribonuclease activity was one-third to one-half of that of r(+)-infected cells. This lower deoxyribonuclease activity was observed also in other hosts or when infection was made with rI or rIII mutants. Presence of chloramphenicol did not allow a continued synthesis of phage deoxyribonucleic acid in rII-infected K(λ). No phage lysozyme was detected nor was any antiphage serum-blocking antigen found in rII-infected K(λ). It is suggested that the rII gene is of significance for the expression of phage-induced late functions in the host K(λ).